Immunotherapy for advanced lung cancer combined with surgery for mediastinal myxofibrosarcoma: a case report - Tetsuya Fukui; Yusuke Wakatsuki; Tadashi Matsukura (Surgical Case Reports, 2019)
Abstract Background It is unclear whether simultaneous primary neoplasm resection and immunotherapy for advanced lung cancer is safe. We report a case of an elderly man with advanced lung cancer and myxofibrosarcoma. Case presentation The advanced lung cancer was treated with pembrolizumab, and partial response was achieved in 3 months. However, the mediastinal cyst enlarged rapidly. We resected the mediastinal tumor and diagnosed it as myxofibrosarcoma. The postoperative course was uneventful. Immunotherapy was resumed after the operation without any adverse effects. No recurrence of mediastinal sarcoma or progression of lung cancer was found until the patient died in an accident 8 months after surgery. Conclusion Surgery for mediastinal sarcoma could be performed safely in combination with immunotherapy for advanced lung cancer.